2021
DOI: 10.1177/14680874211031200
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study with renewable fuels using ECN Spray A and D nozzles

Abstract: The decarbonization process of the automotive industry and the road transport sector has raised the interest on the development of cleaner fuels. A proper characterization of their properties and behavior under different operating conditions is mandatory to achieve an effective implementation in commercial engines. With this objective, the current work presents a comparison of two injectors from the Engine Combustion Network (ECN), namely Spray A and Spray D injectors, in terms of spray characteristics and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…15 Different works have reported an important reduction of in-cylinder soot formation emissions either using neat OME X or blending it with other fuels. [16][17][18][19] Additionally, several authors reported the possibility of using of EGR to reduce nitrogen oxides (NO X ) emissions without affecting soot emissions, 14,20 overcoming the well-known Soot-NO X trade off. As a drawback, OME X has a lower heating value (LHV) lower than fossil Diesel.…”
Section: Introductionmentioning
confidence: 99%
“…15 Different works have reported an important reduction of in-cylinder soot formation emissions either using neat OME X or blending it with other fuels. [16][17][18][19] Additionally, several authors reported the possibility of using of EGR to reduce nitrogen oxides (NO X ) emissions without affecting soot emissions, 14,20 overcoming the well-known Soot-NO X trade off. As a drawback, OME X has a lower heating value (LHV) lower than fossil Diesel.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there might be some potential for further optimization of fuel efficiency by changing the injectors for ones with a higher flowrate (where shorter injections are possible with reduced injection pressures) and performing an optimization with similar emission reduction targets. Conversely, OMEx has a higher vapor pressure and thus a lower liquid penetration length [46], and it has been previously shown that injectors with bigger diameter can increase the spray penetration of OMEx and cause a longer ignition delay [47], these characteristics could contribute in achieving lean-burn conditions for OMEx that improve fuel consumption, similarly to the lambda variations performed in [17]. Nonetheless, further research is needed to verify this hypothesis.…”
Section: Optimization Of Lcf With Equal Ca50mentioning
confidence: 97%
“… Comparison of the effect of nozzle diameter for HVO (left) and OME1 (right) on the characteristic spray parameters. Source:[103] …”
mentioning
confidence: 99%